Acetaldehyde in the Enders triple cascade reaction via acetaldehyde dimethyl acetal - Brusa, Alessandro; Iapadre, Debora; Casacchia, Maria Edith; Carioscia, Alessio; Giorgianni, Giuliana; Magagnano, Giandomenico; Pesciaioli, Fabio; Carlone, Armando (Beilstein Journal of Organic Chemistry, 2023)
Asymmetric organocatalyzed multicomponent reactions represent an important toolbox in the field of organic synthesis to build complex scaffolds starting from simple starting materials. The Enders three-component cascade reaction was a cornerstone in the field and a plethora of organocatalyzed cascade reactions followed. However, acetaldehyde was not shown as a successful reaction partner, probably because of its high reactivity. Herein, we report the Enders-type cascade reaction using acetaldehyde dimethyl acetal, as a masked form of acetaldehyde. This strategy directly converts acetaldehyde, nitroalkenes and enals into stereochemically dense cyclohexenals in good yield and excellent enantioselectivity.
Keywords: acetaldehyde; acetaldehyde dimethyl acetal; cascade reaction; multicomponent reaction; organocatalysis